PROGRAM APLIKASI INVENTORI PADA UD USAHA JAYA MANDIRI - Billy Dewantara; Ery Dewayani; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
UD Usaha Mandiri is a store that located in Tanjung Pinang city which is engaged in selling furniture and raw materials for making sofas. UD Usaha Jaya Mandiri has the potential for miscalculating goods, so there are excesses and shortages of goods, especially raw materials for making sofas. The purpose of